Analisis Agen Serumenolitik Cuka Apel 2,5% Dan Minyak Kelapa Pada Anak Panti Asuhan Putri Aisyiyah Kota Medan Secara In Vitro - Natasya, Savira Ayu; Siregar, Siti Masliana (Universitas Muhammadiyah Sumatera Utara, 2025)
Abstract : Cerumen impaction can occur in all types of ages, both children, adults, and the elderly which are influenced by various factors. Serumenolytic agents can soften and dissolve earwax, one of which is 2.5% Apple Vinegar and Coconut Oil used as alternatives. The purpose of this study is to analyze the effectiveness of cerumenolytic agents Apple Vinegar 2.5% and Coconut Oil as an alternative therapy for serum impaction in children of the Puteri Aisyiyah Orphanage, Medan City, in vitro.This type of research is an in vitro laboratory research using a UV-Vis spectrophotometer and a simple random sampling technique.The mean rank value for the effect of Apple Vinegar is 2.5% (32.40) while Coconut Oil is (16.60).In addition, a P-Value of r (0.000) was obtained 0.005 so that it can be stated that there is a difference in the solubility of the serumen. Which means that the effect of Apple Vinegar is 2.5% greater than that of Coconut Oil. Based on the results of the research that has been conducted, it can be concluded that 2.5% Apple Vinegar has a more reverse effectiveness on serum solubility by showing a higher average value of Coconut Oil at each trial time.